Analysis Of The Limits Of Police Authority In Civil Service Positions Within The Indonesian State System - Arliyanda (Universitas Muhammadiyah Palu, 2026)
This study aims to examine the limits of authority of active members of the Indonesian National Police in holding civilian positions outside the formal police structure and to analyze the implications of such practices for Indonesia’s constitutional system. This issue is significant because Polri is a state institution responsible for law enforcement and public security, and the placement of active police officers in civilian offices may give rise to constitutional concerns, conflicts of interest, and the weakening of the principle of civilian supremacy in a democratic state. The analysis focuses on constitutional–juridical aspects, normative regulations within statutory frameworks, and the practical implementation of assigning active Polri personnel to civilian positions within state institutions and government bodies. This research employs a normative juridical method using statutory, conceptual, and constitutional court decision approaches. The data were collected through a literature review of national legal journals, constitutional law doctrines, and regulations governing the status and authority of Polri. The findings indicate that the existing legal framework concerning the limits of authority for active Polri members to occupy civilian positions remains ambiguous and allows for broad interpretation. Such ambiguity potentially creates legal uncertainty and undermines the principles of neutrality and professionalism of state apparatuses. The study further reveals that decisions of the Constitutional Court play a crucial role in clarifying and reinforcing the boundaries of this authority as part of efforts to maintain the balance of power and strengthen civilian supremacy within Indonesia’s constitutional order. Therefore, clearer and more consistent legal norms are required to ensure that the involvement of Polri in civilian roles remains aligned with constitutional mandates and democratic principles.